2018
DOI: 10.1029/2018gl079137
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Reemergence of Sea Surface Temperature Anomalies in the Global Oceans, Including Tropical Regions Forced by Reemerging Winds

Abstract: Sea surface temperature anomalies (SSTA) in portions of the extratropics are known to recur from one winter to the next without persisting through the intervening summer. Previous studies identified only a limited number of midlatitude regions where this reemergence occurs. Here we find that most of the global oceans exhibit winter‐to‐winter recurrence of SSTA. Indeed, recurrence of SSTA is the default process in the global ocean. Only regions strongly linked to El Niño do not show signs of SST reemergence. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…The shallower MLD of summer periods represents a smaller effective heat capacity with correspondingly larger SSTA sensitivity to variability in atmospheric forcing. Regions characterised by a strong seasonal variation in MLD may also display the phenomenon of re-emergence of winter-to-winter SSTA [9][10][11][12][13] . Winter SST anomalies persist at depth during the summer months below the shallow mixed layer, reemerging in the SSTA the following winter as the summer seasonal thermocline is eroded.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The shallower MLD of summer periods represents a smaller effective heat capacity with correspondingly larger SSTA sensitivity to variability in atmospheric forcing. Regions characterised by a strong seasonal variation in MLD may also display the phenomenon of re-emergence of winter-to-winter SSTA [9][10][11][12][13] . Winter SST anomalies persist at depth during the summer months below the shallow mixed layer, reemerging in the SSTA the following winter as the summer seasonal thermocline is eroded.…”
mentioning
confidence: 99%
“…Winter SST anomalies persist at depth during the summer months below the shallow mixed layer, reemerging in the SSTA the following winter as the summer seasonal thermocline is eroded. In the tropics, SSTA re-emergence is strongly coupled with recurrence of atmospheric drivers, predominantly wind stress 9 , and there is evidence that atmospheric drivers can also affect inter-annual variations in mid-latitude re-emergence 14 . Regional studies have demonstrated the independence of the re-emergence signal from ENSO variability 15 with the strongest re-emergence signals in the NW Pacific, NW Atlantic and Southern Ocean [16][17][18] .…”
mentioning
confidence: 99%
“…Indeed, most of the surface influence on 26.4 σ temperature occurs during the fall/winter months (Figure 1). Following the reemergence mechanism (Alexander & Deser, 1995; Alexander et al., 1999; Byju et al., 2018), winter prior SST anomalies are significantly correlated to the following summer 26.4 σ temperature anomaly. However, the negative correlation of winter SST anomalies to the concurrent downward surface heat fluxes (not shown) suggests that the former is not entirely surface driven.…”
Section: Resultsmentioning
confidence: 99%
“…If recurrent SST anomalies are related to zonal wind stress anomalies as suggested by this study, it can be expected that the recurrence due to the horizontal advection is more prevalent in the region under or near the Aleutian Low. Also, zonal wind anomalies have been suggested to contribute to recurrence of SST anomalies in the tropics (Byju et al, 2018). Moreover, in remote reemergence regions revealed by previous studies (Sugimoto & Hanawa, 2005), temperature anomalies are laterally transported under the subsurface.…”
Section: Discussionmentioning
confidence: 99%